PRIVATISASI BADAN USAHA MILIKNEGARA (BUMN) KEPEMILIKAN SAHAMSEBAGAI UPAYA MENINGKATKANKESEJAHTERAAN UMUM - NEILMAN GINTING (PREMISE LAW JURNAL, 2017)
One of the ways to improve BUMN that is applied in Indonesia is its privatization. By implementing privatization, the distribution of the society’s shares of BUMN becomes more open; it is showed as an effort to invite foreigners to take part in the corporation improvement to create efficiency. According to the research results, it can be concluded that it is necessary to do privatization of BUMN in order to improve efficiency and productivity of BUMN; namely, distributing the shares of BUMN to the society which is certainly aimed to improve the social welfare. It is suggested that privatization be able to change the image of BUMN by implementing GCG (Good Corporate Government) in all levels from the highest until the lowest position. Keywords: Privatization, BUMN (State-Owned Enterprise), Public Welfare